COMPARATIVE ASPECT OF PHRASEOLOGISMS WITH A LINGUISTIC AND LINGUISTIC COMPONENT IN THE SPANISH AND UKRAINIAN LANGUAGES - Akimova, Marta (PROBLEMS OF SEMANTICS, PRAGMATICS AND COGNITIVE LINGUISTICS, 2023)
This article is devoted to the study of the linguistic and cultural component in the phraseological units of the Spanish and Ukrainian languages. Phraseologisms were considered as an important aspect of language culture and studied from the point of view of cultural features of the historical development of each of these languages. The article analyzes similarities and differences in the use of idioms in the two languages and reveals the influence of cultural and historical contexts on their interpretation. The methods of comparative analysis were used to identify common and unique features of phraseological units in Spanish and Ukrainian languages, and also provide specific examples that illustrate the peculiarities of the use of phraseological units in each language. The results of this study help to better understand the relationship between language and culture, as well as contribute to the deepening of knowledge about the phraseology of the Spanish and Ukrainian languages. This article is useful for linguists, translators, and anyone interested in the study of Spanish and Ukrainian languages and cultures._______________References:• Grefa, Elvia, Gorchynska, L. V. Phraseologisms of the Ukrainian and Spanish languages. common and different. VNTU Conferences, https://conferences.vntu.edu.ua › download.• Diachenko, A. V. Phraseologisms in the context of language culture (Kharkiv: V. N. Karazin KhNU Publishing House, 2019), 132.• Kulish, O. S. Spanish Phraseology (Madrid: Editions Catalunya, 2016), 298.• Linguistic analysis of phraseological units in the cultural context, ed. S. A. Lyapiny, K. V. Shamrai (Kyiv: Kyiv University Publishing House, 2017), 185.• Popovych, V. A. Ukrainian Phraseology (Kyiv: "Akademiya" Publishing House, 2015),• Fuentes, S. Grammar of the Spanish Language (Madrid: Editions Sm, 2008), 321.• Verba, Galyna. Curso de lexicologia comparada (espanol-ucraniano) (Vinnitsia: Nova Knyha, 2021), 232.• Verbá, G. La motivation del significado de las palabras en español y en ucraniano (un enfoque contrastivo). V Congress of Hispanists of Ukraine. Actas. Dnipropetrovsk, October 3-4, 2014. Embassy of Spain in Ukraine, Ministerio de Asuntos Exteriores, AECID: 138-146.• Balabayeva, V. G. What makes the house rich: Spanish proverbs and sayings and their Ukrainian equivalents (Vinnytsia: Globus-press, 2008), 384.• Prieto Grande, M. Hablando en plata de modismos y metáforas culturales (Madrid: Editorial Edinumen, 2007), 102.• Diccionario de la Real Academia Española, http://buscon.rae.es/
Keywords: phraseology, comparative analysis, linguistic culture, linguistic and cultural analysis, linguistic and cultural component, cultural identity